Analisis Penerapan Prinsip Akuntansi Syariah Pada Dinas Perindustrian, Energi Dan Sumber Daya Mineral Kabupaten Gayo Lues - Ranti Oyana; Kusmilawaty Kusmilawaty (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2023)
Theoretical and practical advances in Islamic accounting have been made in Indonesia. The Islamic finance industry includes Islamic banks, Islamic insurance companies, even Islamic stocks. However, in the non-financial sector, Islamic accounting is not widely practiced. In today's World, Islamic accounting is widely used because its principles consider not only the relationship of man to man, but also the relationship of man to God, man to man, and nature to nature. Aceh is one of the areas that adheres to strong Islamic law. Acehnese people uphold Islamic values in their lives, thus making aceh one of the privileged areas, where aceh can make local regulations based on Islamic law called Qanun aceh. Basically, aceh has applied many sharia accounting principles and systems to its local regulations, so that currently all financial institutions in aceh are sharia-based. According to Karim, the terminology definition of Sharia is â€œregulations and laws that have been outlined by Allah SWT, or have been outlined principally and charged to the Muslims to obey them, so that this Sharia is taken by Muslims as a liaison between them with Allah SWT and between them with humans.â€ (Karim, 2010). Aceh has a privilege that can make local regulations in accordance with Islamic law, should be able to apply the concept of Islamic government, where local government activities are carried out in accordance with the concept of Islamic law but not contrary to the legislation of the Indonesian government system, as well as Sharia governance signifies not violating international law and Human Rights.